Remoção do agrotóxico organofosforado Clorpirifós usando processo oxidativo avançado - Oliveira, André Gadelha de (2011)
This study investigated to advanced oxidation process (POA) for removal of organophosphorus pesticide chlorpyrifos. Reactor system, in laboratory and pilot scale, have been studied. In the first stage, in laboratory scale, were performed studies of the parameters temperature, pH, dosage of hydrogen peroxide, pesticide concentration and inhibitory effects of anions. The results indicated that a temperature of 45 oC showed a better pesticide removal using only UV radiation, however, for the system UV/H2O2, the temperature did not affect the process. The pH effect was studied for H2O2 and UV/H2O2 systems and was observed that pH did not affect the efficiency of the system UV/H2O2. In addition, at pH 10 a better performance for the system H2O2 on the removal of pesticide was observed. Hydrogen peroxide dosage also was studied, and 1,5g/L dosage was most efficient in the pesticide removal. The inhibitory effect of the anions, such as chloride, nitrate, sulfate and bicarbonate was not significantive in the pesticide removal at a time of 480 minutes. In contrast, presence of carbonate anion at 60 minutes, there was a total transformation of chlorpyrifos in an unknown compound. The second stage was conducted on a pilot scale, and flow rate were studied (1.5; 2.0 and 3.0 L/min). The final concentration of pesticide at 480 minutes, for the three flow, were 0.30; 0.43 and 0.5 mg/L, respectively. The turbidity and color removal was efficient for all flows studied, in contrast with the DQO removal.